The relationship between work-life balance and psychological well-being: an empirical study of metro rail travelers working in the information technology sector - Prasad, K. D. V.; Rao, Mruthyanjaya; Vaidya, Rajesh; Sriyogi, Kottala; Singh, Shivoham; Srinivas, Ved (Frontiers in Psychology, 2025)
ObjectivesTo investigate the relationship between work–life balance and the psychological well-being of metro rail travelers working in the information technology sector. The study also examined occupational stress as a pathway between work-life balance and psychological well-being. The study also investigated the impact of occupational stress and work–life balance on the psychological well-being of metro travelers who work in the information technology sector, modeling lower- and higher-order constructs.MethodsA quantitative survey method was used, and the data were gathered from information technology employees who frequently travel on Metro Rail to commute to the office and return home when the COVID-19 pandemic peaked in India in 2022. A structured questionnaire was developed, and a link was provided to the IT sector employees visiting almost all the metro stations in Hyderabad, an Indian Metro, to measure 8 reflective constructs. The data were gathered via random sampling, and the questionnaires were randomly distributed to the different IT sector companies. The valid responses of 500 participants were analyzed for structural equation modeling. The eight reflective constructs in the study are occupational stress, the 3 constructs of work–life balance—“work interference with personal life, personal life interference with work and work–personal life enhancement”—and the four constructs of psychological well-being autonomy, self-acceptance, positive relations, and environmental mastery.ResultsThe SEM results for the lower-order constructs indicate that the impact of occupational stress on psychological well-being was statistically significant (p < 0.005), as were the two constructs of psychological well-being, environmental mastery, and self-acceptance (p < 0.001; p < 0.05). With respect to the impact of the work–life balance constructs, the impacts of the WIPL, WPLE, and PLIW work–life balance constructs were statistically significant (p < 0.05; p < 0.001, respectively) for all four psychological well-being constructs. Occupational stress partially mediated the relationship between work–life balance and psychological well-being, as both the direct and indirect effects were statistically significant when the higher-order constructs work–life balance and psychological well-being were tested. The direct effects of occupational stress and work–life balance on psychological well-being are statistically significant (p < 0.05, p < 0.001).ConclusionThe authors suggest framing policies to mitigate occupational stress and enhance the psychological well-being and work–life balance of employees in the information technology sector.